PROMOSI KESEHATAN TENTANG DETEKSI DINI ANEMIA PADA REMATRI DAN IBU HAMIL DI PUSKESMAS BANJARBARU UTARA - Sarifah Nazla Nabelia; Nurul Mardiati; Feni Narulita (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Adolescent girls (Rematri) need adequate iron intake to prevent iron deficiency during menstruation, which can lead to growth disorders, anemia, and weakened immune function. Prolonged iron deficiency increases the risk of anemia during pregnancy, potentially causing complications for both mother and fetus, including death. This activity aimed to raise public awareness and understanding of anemia, focusing on adolescent girls and pregnant women. The targets were residents of Loktabat and Mentaos, especially Rematri aged 12–21 years and pregnant women visiting the North Banjarbaru Community Health Center. Health promotion was delivered through a lecture method using leaflets, involving 15 participants from both target groups. The activity showed positive outcomes, with a 29.33% increase in knowledge based on the average pretest score of 64.00% and posttest score of 93.33%. Statistical analysis using a paired sample t-test showed a significant improvement (p < 0.0001).